High-dielectric modified sodium niobate-based lead-free dielectric ceramic as well as preparation method and application thereof
By introducing Bi3+, Sr2+, Fe3+ and Ti4+ into the NaNbO3 matrix, the disorder degree and the formation of antiferroelectric domains are increased, and the problem of low dielectric constant of existing lead-free dielectric ceramic materials is solved, and the effects of high dielectric constant and low dielectric loss are achieved.
Patent Information
- Application Number
- CN202411913160.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
The existing lead-free dielectric ceramic materials have low dielectric constants and are difficult to meet the needs of high energy density and high power density.
By introducing Bi3+, Sr2+, Fe3+ and Ti4+ into the NaNbO3 matrix, the disorder of A and B positions is increased, short-range ordered and nanoscale antiferroelectric domains are formed, and dielectric properties are improved.
It significantly improves the dielectric constant, reduces the dielectric loss, and meets the needs of high energy density and high power density.
Smart Images

Figure CN119683997A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dielectric materials, and more specifically relates to a high-dielectric modified sodium niobate-based lead-free dielectric ceramic and a preparation method and application thereof. Background Art
[0002] The growing dielectric material market requires higher performance and more efficient dielectric materials with better functionality and lower cost. Mobile electronic devices, hybrid electric vehicles, medical implants and other technologies have high requirements for lightweight, compact and high energy density capacitors. Existing energy storage technologies include dielectric capacitors, supercapacitors and fuel cells, among which dielectric capacitors have incomparable advantages due to their high power density and ultra-long cycle life generated by their fast charge and discharge rates. The core of dielectric capacitors is dielectric materials, and high dielectric constant is one of the ways to obtain high energy storage performance. Ceramic-based dielectric capacitors have been widely used in high-power and pulse power electronic systems such as electromagnetic guns, electromagnetic launch platforms, and high-power accelerators due to their outstanding advantages such as ultra-fast charge and discharge rates, high power density, superior thermal stability, anti-fatigue characteristics and high operating voltage, and have attracted widespread attention.
[0003] Among ceramic-based dielectric capacitors, the PbZrO3-based antiferroelectric materials with higher dielectric constant, higher breakdown field strength and higher efficiency have the best dielectric properties, such as (Pb, La)(Zr, Sn) O3 and (Pb, La, Ca)(Zr, Sn) O3. However, about 70wt% of the raw materials of these materials are lead oxide, which will seriously affect human health and cause irreversible damage to the environment. Therefore, lead-free dielectric capacitors have been increasingly studied. Among the known lead-free ceramic materials, the NaNbO3-based ceramic dielectric capacitor with a perovskite structure is a noteworthy environmentally friendly product with excellent piezoelectric and energy storage properties. Pure NaNbO3 ceramics do not have stable relaxation behavior at ambient temperature. In some schemes, NaCO3, Nb2O5, CaCO3, SiO2, B2O3, and HfO2 are used as raw materials to synthesize ceramic samples, referred to as NNCSB-H1. Although it has a high breakdown strength, its dielectric constant is low, only 112 at 1kHz at room temperature; in some schemes, NaNbO3 is used as the main matrix material, BiZn 0.5 Ti 0.5 As relaxation modifier, LiNiMnO is a modification additive. The synthesized material improves the compactness of the porcelain body and increases the breakdown electric field strength. By adding BiZn 0.5 Ti 0.5 , Li2NiMnO3 is chemically modified to improve the stability of the antiferroelectric phase, but its dielectric constant is low, only about 700 at 1kHz at room temperature.
[0004] In view of the above problems, how to provide a high dielectric modified sodium niobate-based lead-free dielectric ceramic material has become a difficult problem that technicians in this field need to solve urgently. Summary of the invention
[0005] The purpose of the present invention is to provide a high dielectric modified sodium niobate-based lead-free dielectric ceramic and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is to provide a high dielectric modified sodium niobate-based lead-free dielectric ceramic material, wherein the chemical formula of the high dielectric modified sodium niobate-based lead-free dielectric ceramic is x(Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 )O3-(1-x)NaNbO3; wherein the value of x is 0.03 to 0.15.
[0008] The present invention introduces Bi into the NaNbO3 matrix 3+ , Sr 2+ , Fe 3+ and Ti 4+ , due to the different valence states and ionic radii, the disorder of the A and B sites will increase simultaneously, leading to the formation of short-range order and nanoscale antiferroelectric domains and enhanced relaxation properties. 2+ Similar, Bi 3+ The outermost electron configuration is 6s 2 6p 0 , so Bi 3+ The 6p orbital and O 2- The hybridization between the 2p orbitals helps to maintain a large P max Finally, the test at room temperature showed that the dielectric constant of the modified ceramic material was significantly improved compared with that of the NaNbO3 material, and the dielectric loss was lower.
[0009] Optionally, the value of x is 0.03, 0.06, 0.09, 0.12 or 0.15.
[0010] As the value of x increases, the antiferroelectricity of the modified ceramic material also increases, which is reflected in the dielectric constant and dielectric loss of the modified ceramic material.
[0011] The second technical solution of the present invention is to provide a method for preparing a high dielectric modified sodium niobate-based lead-free dielectric ceramic material, the steps comprising:
[0012] NaCO3, Nb2O5, Bi2O3, Fe2O3, SrCO3 and TiO2 are mixed and wet-milled using ethanol as a milling medium, followed by drying and calcining to obtain the high-dielectric modified sodium niobate-based lead-free dielectric ceramic material;
[0013] The amounts of NaCO3, Nb2O5, Bi2O3, Fe2O3, SrCO3 and TiO2 are prepared according to the above chemical formula.
[0014] Furthermore, the wet ball milling treatment is carried out at a rotation speed of 400 to 600 rpm and for a time of 12 to 24 hours.
[0015] Furthermore, the drying temperature is 100° C. and the drying time is 12 hours.
[0016] Furthermore, the sintering temperature is 800-900° C. and the sintering time is 1-3 hours.
[0017] The third technical solution of the present invention is to provide a method for preparing a high dielectric modified sodium niobate-based lead-free dielectric ceramic, the steps comprising:
[0018] The high dielectric modified sodium niobate-based lead-free dielectric ceramic material is subjected to wet ball milling treatment using ethanol as a ball milling medium, and then subjected to pressing and sintering to obtain the high dielectric modified sodium niobate-based lead-free dielectric ceramic.
[0019] Furthermore, the compression molding pressure is 10-20 MPa and the time is 5 minutes.
[0020] Furthermore, the sintering temperature is 1000-1300° C., and the sintering time is 1-2 hours.
[0021] The fourth technical solution of the present invention: provides a high dielectric modified sodium niobate-based lead-free dielectric ceramic, wherein the high dielectric modified sodium niobate-based lead-free dielectric ceramic is prepared by the above-mentioned preparation method.
[0022] The fifth technical solution of the present invention is to provide a high dielectric modified sodium niobate-based lead-free dielectric ceramic material.
[0023] The present invention discloses the following technical effects:
[0024] The invention introduces different elements into the A and B positions of the sodium niobate ceramic base to obtain a smaller tolerance factor to stabilize the antiferroelectric phase of the NaNbO3-based system. Meanwhile, the preparation process is simple and controllable, low-cost and green.
[0025] Compared with pure sodium niobate ceramic-based materials, the present invention introduces Bi into the NaNbO3 matrix. 3+ , Sr 2+ , Fe 3+and Ti 4 + Due to different valence states and ionic radii, the disorder at the A and B sites will increase simultaneously. Tests at room temperature show that the dielectric constant of the modified ceramic material is significantly improved compared with that of the NaNbO3 material, and the dielectric loss is lower. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0027] Figure 1 The SEM images and average particle sizes of the high dielectric modified sodium niobate-based lead-free dielectric ceramics prepared in Examples 1 to 5, wherein (a) is the SEM image of Example 1, (b) is the SEM image of Example 2, (c) is the SEM image of Example 3, (d) is the SEM image of Example 4, (e) is the SEM image of Example 5, and (f) is the average particle size;
[0028] Figure 2 XRD patterns of high dielectric modified sodium niobate-based lead-free dielectric ceramics prepared in Examples 1 to 5;
[0029] Figure 3 The dielectric constants of the ceramics prepared for Examples 1 to 5 and Comparative Examples 1 to 2;
[0030] Figure 4 The dielectric loss of the ceramics prepared in Examples 1 to 5 and Comparative Examples 1 to 2. DETAILED DESCRIPTION
[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0032] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0033] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0034] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0036] Unless otherwise specified, the "room temperature" or "normal temperature" referred to in the specific embodiments of the present invention refers to 25±2°C.
[0037] The NaCO3, Nb2O5, Bi2O3, Fe2O3, SrCO3 and TiO2 used in the specific implementation manner of the present invention are all provided by Shanghai Titan Technology Co., Ltd.
[0038] The present invention provides a method for preparing a high dielectric modified sodium niobate-based lead-free dielectric ceramic, the steps comprising:
[0039] S1, according to the general formula x(Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 )O3-(1-x)NaNbO3 weigh NaCO3, Nb2O5, Bi2O3, Fe2O3, SrCO3 and TiO2 for later use; wherein the value of x is 0.03 to 0.15;
[0040] S2. Weighed NaCO3, Nb2O5, Bi2O3, Fe2O3, SrCO3 and TiO2 are mixed and wet-milled with ethanol as the milling medium, followed by drying at 100°C for 12 hours, and the dried powder is placed in a heat treatment furnace and pre-sintered at 700-900°C for 1-3 hours to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic material; wherein the wet-milling speed is 400-600 rpm and the time is 12-24 hours;
[0041] S3. The high dielectric modified sodium niobate-based lead-free dielectric ceramic material is wet-milled using ethanol as a ball-milling medium, and then dried at 100°C for 12 hours. The dried powder is then pressed into shape at a pressure of 10 to 20 MPa for 5 minutes, and finally sintered at 1000 to 1300°C for 1 to 2 hours to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic; wherein the rotation speed of the wet ball milling treatment is 400 to 600 rpm, and the time is 12 to 24 hours.
[0042] In some specific embodiments, the chemical formula is 0.03 (Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 )O3-0.97NaNbO3, the sintering temperature of step S3 is 1275°C, and the sintering time is 1h.
[0043] In some specific embodiments, the chemical formula is 0.06 (Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 )O3-0.94NaNbO3, the sintering temperature of step S3 is 1250°C, and the sintering time is 1.2h.
[0044] In some specific embodiments, the chemical formula is 0.09 (Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 )O3-0.91NaNbO3, the sintering temperature of step S3 is 1225°C, and the sintering time is 1.4h.
[0045] In some specific embodiments, the chemical formula is 0.12(Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 )O3-0.88NaNbO3, the sintering temperature of step S3 is 1220°C, and the sintering time is 1.6h.
[0046] In some specific embodiments, the chemical formula is 0.15 (Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 )O3-0.85NaNbO3, the sintering temperature of step S3 is 1175°C, and the sintering time is 2h.
[0047] The high dielectric modified sodium niobate-based lead-free dielectric ceramic materials obtained according to different chemical formula ratios are placed in sintering furnaces at different temperatures for heat preservation and sintering, ensuring that the ceramic raw materials obtained by each chemical formula ratio can be effectively sintered into ceramics.
[0048] Example 1
[0049] The general chemical formula is 0.03(Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 The preparation steps of )O3-0.97NaNbO3 high dielectric modified sodium niobate-based lead-free dielectric ceramics include:
[0050] S1. Weigh 514g NaCO3, 1290g Nb2O5, 55.9g Bi2O3, 19.2g Fe2O3, 8.9g SrCO3 and 4.8g TiO2 of raw materials, ball mill (400rpm) in excess anhydrous ethanol for 24h, dry at 100℃ for 12h, and then pre-sinter at 800℃ for 3h in a closed condition to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic material;
[0051] S2. The high dielectric modified sodium niobate-based lead-free dielectric ceramic material was ball-milled (400 rpm) in anhydrous ethanol for 12 h, dried at 100°C for 12 h, passed through a 150-mesh sieve, and then pressed into a thin sheet with a thickness of 1 mm and a diameter of 10 mm using a powder tablet press. The pressure was 15 MPa and the holding time was 5 min. Finally, it was sintered at 1275°C for 1 h and cooled to room temperature to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic, recorded as 0.97NN-0.03BSFT.
[0052] Example 2
[0053] The chemical formula is 0.06(Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 The preparation steps of )O3-0.94NaNbO3 high dielectric modified sodium niobate-based lead-free dielectric ceramics include:
[0054] S1. Weigh 498g NaCO3, 1250g Nb2O5, 111.9g Bi2O3, 38.3g Fe2O3, 17.7g SrCO3 and 9.6g TiO2 of raw materials, ball mill (450rpm) in excess anhydrous ethanol for 24h, dry at 100℃ for 12h, and then pre-sinter at 800℃ for 3h in a closed condition to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic material;
[0055] S2. The high dielectric modified sodium niobate-based lead-free dielectric ceramic material was ball-milled (450 rpm) in anhydrous ethanol for 12 h, dried at 100°C for 12 h, sieved through a 150-mesh sieve, and then pressed into a thin sheet with a thickness of 1 mm and a diameter of 10 mm using a powder tablet press. The pressure was 15 MPa and the holding time was 5 min. Finally, it was sintered at 1250°C for 1.2 h and cooled to room temperature to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic, recorded as 0.94NN-0.06BSFT.
[0056] Example 3
[0057] The chemical formula is 0.09(Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 The preparation steps of )O3-0.91NaNbO3 high dielectric modified sodium niobate-based lead-free dielectric ceramics include:
[0058] S1. Weigh 482g NaCO3, 1210g Nb2O5, 167.8g Bi2O3, 57.5g Fe2O3, 26.6g SrCO3 and 14.4g TiO2 of raw materials, ball mill (500rpm) in excess anhydrous ethanol for 24h, dry at 100℃ for 12h, and then pre-sinter at 800℃ for 3h in a closed condition to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic material;
[0059] S2. The high dielectric modified sodium niobate-based lead-free dielectric ceramic material was ball-milled (500 rpm) in anhydrous ethanol for 12 h, dried at 100°C for 12 h, sieved through a 150-mesh sieve, and then pressed into a thin sheet with a thickness of 1 mm and a diameter of 10 mm using a powder tablet press. The pressure was 15 MPa and the holding time was 5 min. Finally, it was sintered at 1225°C for 1.4 h and cooled to room temperature to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic, recorded as 0.91NN-0.09BSFT.
[0060] Example 4
[0061] The general chemical formula is 0.12(Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 The preparation steps of )O3-0.88NaNbO3 high dielectric modified sodium niobate-based lead-free dielectric ceramics include:
[0062] S1. Weigh 466g NaCO3, 1169.6g Nb2O5, 223.7g Bi2O3, 76.7g Fe2O3, 35.4g SrCO3 and 19.2g TiO2 as raw materials, ball mill (550rpm) in excess anhydrous ethanol for 24h, dry at 100℃ for 12h, and then pre-sinter at 800℃ for 3h in a closed condition to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic material;
[0063] S2. The high dielectric modified sodium niobate-based lead-free dielectric ceramic material was ball-milled (550 rpm) in anhydrous ethanol for 12 h, dried at 100°C for 12 h, sieved through a 150-mesh sieve, and then pressed into a thin sheet with a thickness of 1 mm and a diameter of 10 mm using a powder tablet press. The pressure was 15 MPa and the holding time was 5 min. Finally, it was sintered at 1200°C for 1.6 h and cooled to room temperature to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic, recorded as 0.88NN-0.12BSFT.
[0064] Example 5
[0065] The chemical formula is 0.15(Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 The preparation steps of )O3-0.85NaNbO3 high dielectric modified sodium niobate-based lead-free dielectric ceramics include:
[0066] S1. Weigh 450g NaCO3, 1130g Nb2O5, 279.6g Bi2O3, 96g Fe2O3, 44.3g SrCO3 and 24g TiO2 of raw materials, ball mill (600rpm) in excess anhydrous ethanol for 24h, dry at 100℃ for 12h, and then pre-sinter at 800℃ for 3h in a closed condition to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic material;
[0067] S2. The high dielectric modified sodium niobate-based lead-free dielectric ceramic material was ball-milled (600 rpm) in anhydrous ethanol for 12 h, dried at 100°C for 12 h, sieved through a 150-mesh sieve, and then pressed into a thin sheet with a thickness of 1 mm and a diameter of 10 mm using a powder tablet press. The pressure was 15 MPa and the holding time was 5 min. Finally, it was sintered at 1175°C for 2 h and cooled to room temperature to obtain a high dielectric modified sodium niobate-based lead-free dielectric ceramic, recorded as 0.85NN-0.15BSFT.
[0068] Figure 1The SEM images and average particle sizes of the high dielectric modified sodium niobate-based lead-free dielectric ceramics prepared in Examples 1 to 5, wherein (a) is the SEM image of Example 1, (b) is the SEM image of Example 2, (c) is the SEM image of Example 3, (d) is the SEM image of Example 4, (e) is the SEM image of Example 5, and (f) is the average particle size. It can be seen from the figure that with the change of x value, the particle size of the composite first decreases and then increases. This is because the different sintering temperatures affect the growing particle size, and Bi2O3 as a sintering agent affects the sintering temperature. With the increase of Bi2O3 content, the sintering temperature gradually decreases.
[0069] Figure 2 The XRD diagrams of the high dielectric modified sodium niobate-based lead-free dielectric ceramics prepared in Examples 1 to 5 show that the prepared products are pure perovskite structures without a second phase.
[0070] Comparative Example 1
[0071] Preparation of NaNbO3 materials:
[0072] S1. The raw materials Bi2O3 and Nb2O5 are heated (1000℃) in excess NaCl at a mass ratio of 1:1 to form a two-dimensional crystalline Bi 2.5 Na 3.5 Nb5O 18 (BiNN5) precursor, BiNN5 and NaCl are mixed in a mass ratio of 1:1.5 and then heated (900°C, 180min), and then the mixture is washed, filtered, and dried (80°C, 120min) to obtain NaNbO3.
[0073] Comparative Example 2
[0074] Preparation of (1-x)NaNbO3-xLiTaO3 materials:
[0075] S1. Weigh and mix NaNbO3 powder and LiTaO3 powder in the general formula (1-x)NaNbO3-xLiTaO3 to obtain a complete batch, wherein x=0.12.
[0076] S2. Ball mill all ingredients in excess anhydrous ethanol (400 rpm) for 24 h, dry at 100 ° C for 12 h, pass through a 150-mesh sieve, and then press into a sheet with a thickness of 1 mm and a diameter of 10 mm using a powder tablet press. The pressure is 15 MPa and the holding time is 5 min. Finally, sinter at 1200 ° C for 2 h and cool to room temperature to obtain (1-x)NaNbO3-xLiTaO3 ceramics.
[0077] Test example
[0078] The dielectric properties of the materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were tested at room temperature using a broadband dielectric impedance spectrometer (Concept 80, Novocontrol, Germany). The results are shown in Tables 1 and Figures 3-4 shown.
[0079] Table 1
[0080]
[0081] When the frequency is 10 3 The dielectric constants and dielectric losses of Examples 1 to 5 and Comparative Examples 1 to 2 at 10 Hz are shown in Table 1. 3 Under the condition of Hz, the dielectric constant of comparative example 1 is 230, the dielectric loss is 0.3200, the dielectric constant of comparative example 2 is 256, the dielectric loss is 0.1200, and the Bi is introduced in Examples 1 to 5. 3+ , Sr 2+ , Fe 3+ and Ti 4+ After that, the dielectric constant of the material is much higher than that of Comparative Examples 1-2.
[0082] Figure 3 The dielectric constants of the ceramics prepared in Examples 1 to 5 and Comparative Examples 1 to 2.
[0083] Figure 4 The dielectric loss of the ceramics prepared in Examples 1 to 5 and Comparative Examples 1 to 2.
[0084] Depend on Figures 3-4 It can be seen that the dielectric constants of embodiments 1 to 5 are much higher than those of comparative embodiments 1 and 2, and the dielectric constant of the embodiments is optimal when x=0.12. The dielectric loss of the embodiments is much smaller than that of the comparative embodiments. When x=0.12, the dielectric loss of the embodiments is minimal and is not greatly affected by frequency changes.
[0085] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0086] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high dielectric modified sodium niobate-based lead-free dielectric ceramic material, characterized in that: The chemical formula of the high dielectric modified sodium niobate-based lead-free dielectric ceramic is x(Bi 0.8 Sr 0.2 )(Fe 0.8 Ti 0.2 )O3-(1-x)NaNbO3; wherein the value of x is 0.03 to 0.
15.
2. A method for preparing a high dielectric modified sodium niobate-based lead-free dielectric ceramic material, characterized in that the steps include: NaCO3, Nb2O5, Bi2O3, Fe2O3, SrCO3 and TiO2 are mixed and wet-milled using ethanol as a milling medium, followed by drying and calcining to obtain the high-dielectric modified sodium niobate-based lead-free dielectric ceramic material; The amounts of NaCO3, Nb2O5, Bi2O3, Fe2O3, SrCO3 and TiO2 are prepared according to the general chemical formula of the high dielectric modified sodium niobate-based lead-free dielectric ceramic material according to claim 1.
3. The preparation method according to claim 2, characterized in that: The wet ball milling process is performed at a rotation speed of 400 to 600 rpm for a time of 12 to 24 hours; and / or, The drying temperature is 100° C. and the drying time is 12 hours; and / or, The sintering temperature is 800-900° C. and the sintering time is 1-3 hours.
4. A method for preparing a high dielectric modified sodium niobate-based lead-free dielectric ceramic, characterized in that the steps include: The high dielectric modified sodium niobate-based lead-free dielectric ceramic material according to claim 1 is subjected to wet ball milling treatment using ethanol as a ball milling medium, and then subjected to pressing and sintering to obtain the high dielectric modified sodium niobate-based lead-free dielectric ceramic.
5. The preparation method according to claim 4, characterized in that: The pressure of the compression molding is 10-20 MPa.
6. The preparation method according to claim 4, characterized in that: The sintering temperature is 1000-1300° C. and the sintering time is 1-2 hours.
7. A high dielectric modified sodium niobate-based lead-free dielectric ceramic, characterized in that: The high dielectric modified sodium niobate-based lead-free dielectric ceramic is prepared by the preparation method according to any one of claims 4 to 6.
8. Use of the high dielectric modified sodium niobate-based lead-free dielectric ceramic material according to claim 1 or the high dielectric modified sodium niobate-based lead-free dielectric ceramic according to claim 7 in a capacitor.